Tailoring anisotropy and domain structure in amorphous TbCo thin films through combinatorial methods. (9th December 2015) - Frisk, Andreas; Magnus, Fridrik; George, Sebastian; Arnalds, Unnar B; Andersson, Gabriella
Abstract: We apply an in-plane external magnetic field during growth of amorphous TbCo thin films and examine the effects on the magnetic anisotropy and domain structure. A combinatorial approach is employed throughout the deposition and analysis to study a continuous range of compositions between 7–95 at.% Tb. Magnetometry measurements show that all samples have a strong out-of-plane anisotropy, much larger than any in-plane components, regardless of the presence of a growth field. However, magnetic force microscopy demonstrates that the growth field does indeed have a large effect on the magnetic domain structure, resulting in elongated domains aligned along the imprinting field direction. The results show that the anisotropy can be tuned in intricate ways in amorphous TbCo films giving rise to unusual domain structures. Furthermore the results reveal that a combinatorial approach is highly effective for mapping out these material properties.